The Implications of Judicial Decisions on Child Custody Post-Divorce: An Islamic Legal Perspective and Its Contribution to Child Welfare within the Context of Sustainable Development Goals (SDGs) - Lazuarman; Ikromi, Zul; Ismail, Hidayatullah (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study investigates the implications of judicial decisions on child custody post-divorce in the Religious Court of Pekanbaru, Indonesia, through an analysis of five selected cases. Using a juridical-sociological approach, the research examines how Islamic legal principles and socio-cultural factors influence child custody rulings, particularly focusing on the principle of the best interest of the child. The findings reveal that judges prioritize emotional stability, favoring mothers as custodians for younger children, and take into account socio-cultural factors such as traditional gender roles in determining custody. Practical challenges in implementing these decisions, particularly concerning child support and visitation rights, are also highlighted. Through document analysis, interviews, and observations, this study identifies the gap between legal rulings and their real-world application, emphasizing the need for stronger enforcement mechanisms. The research contributes to the understanding of child custody decisions within the framework of Islamic family law and offers implications for improving child welfare practices, especially in post-divorce contexts. This study provides valuable insights into the intersection of Islamic law, socio-cultural factors, and child welfare, contributing to the academic discourse on child custody in Islamic legal systems.